Diagnostic performance of simplified intravoxel incoherent motion DWI for breast lesions (Annals of Medical Research, 2025)
Aim: To assess the success of 3b-value simplified intravoxel incoherent motion (SI-IVIM) diffusion-weighted imaging (DWI) in distinguishing malignant from benign breast lesions.Materials and Methods: Sixty-four breast lesions in 59 women were retrospectively analyzed. Patients with MRI-negative lesions, lesions smaller than 8 mm, poor-quality DWI, or indeterminate lesions without surgical excision were excluded. All MRIs scans were conducted using a 1.5 T MRI scanner, including DWI (b values: 0, 100, 800, and 1500 s/mm2), and dynamic contrast-enhanced sequences (DCE-MRI). Lesions were segmented manually using the ITKsnap program with the help of DCE-MRI, and volumetric mask images (VOI) were generated. Different apparent diffusion coefficient (ADC) values and IVIM parameters, D=ADC (100,1500) and f= f(0, 50, 800), were computed. The diagnostic performances of different ADC values and IVIM parameters were compared to define sensitivity, specificity and the optimal cut-off values.Results: Maximum (max) ADC100, median (med) ADC800, med ADC1500, med f and minimum (min) f values showed significant differences between benign and malignant breast lesions. Med D and min D were lower in the malignant group; however, this difference did not reach statistical significance. The diagnostic performances of med f (AUC= 0.79) and min f (AUC= 0.76) were superior to those of the conventional ADC value (ADC800, AUC= 0.74) in the ROC curve analysis.  However, in the DeLong test analysis, neither med f nor min f demonstrated statistically significant diagnostic superiority over the other parameters.Conclusion: The SI-IVIM parameters showed no significant diagnostic superiority over the ADC value in differentiating malignant breast lesions.
Keywords: Breast neoplasms; Diffusion magnetic resonance imaging; Simplified IVIM; Intravoxel-incoherent motion